Exploring Independent Economic Potential Through Digital Screen Printing as a Business Identity of Tanjung Harapan Village Community, Labuhanbatu Regency - Kembaren, Mardiah Mawar; Lubis, M. Husnan; Lubis, Zulfan; Yudhistira, Eko; Gunaika, Raka (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
An independent economy for a village aims to improve the quality of life. One way is by entrepreneurship, namely running your own economic business, creating new business units, and creating innovations that generate profits for the village, by the village, and for the village. Products produced by BUMDes often do not have the identity of the products they produce. The lack of awareness of the village community about their business brand image will make it difficult for buyers to buy the same product in the future. Therefore, through activities and creativity produced by digital screen printing techniques, the products produced by BUMDes finally have a business identity that is easy for buyers to find again, and can even order BUMDes products repeatedly. This service will be carried out in Tanjung Harapan Village, Pangkatan District, Labuhanbatu Regency. The method used in this service is community empowerment in the form of education on the importance of creating local economic independence, as well as the implementation of digital packaging screen printing designs for products produced by BUMDes in the food, beverage, and handicraft sectors.